Numbness and Weakness Recovered at a Less Extent in Patients with Lumbar Disc Herniation after Percutaneous Endoscopic Lumbar Discectomy - Yuming Wang; Fuqiang Gao; Haibo Zou (Pain Research and Management)
Background. Patients with lumbar disc herniation (LDH) may present with motor disorders and various sensory disorders, among which pain and numbness are the most common ones. Percutaneous endoscopic lumbar discectomy (PELD) is reported to be both safe and effective. However, most of the previous studies focused on the recovery of pain, and the relief extent of numbness and weakness has rarely been reported. The Sciatica Bothersomeness Index (SBI) is a self-assessment tool for LDH patients. It has demonstrated acceptable reliability, construct validity, and responsiveness. Objectives. Our aim was to explore the curative effect of percutaneous endoscopic lumbar discectomy and to compare the various extent of relief among pain, numbness, and weakness. Methods. The medical records of patients admitted for LDH from September 2016 to December 2018 were collected, and the patients were followed up for 3 months to evaluate the relief of their clinical symptoms. Preoperative and postoperative total scores and subitem scores of SBI were compared to evaluate the relief of pain, numbness, and weakness. Surgical outcomes of PELD were evaluated by the Nakai score, and patients were divided into two groups accordingly, which were the relief group (excellent and good in the Nakai score) and the less relief group (fair and poor in the Nakai score). Risk factors for PELD outcomes and preoperative presence of numbness and/or weakness were analyzed by the logistic model, and p value less than 0.05 was considered significant. Results. A total of 86 patients met the inclusion criteria and acquired 3 months follow-up. Relief extent of pain, numbness, and weakness, was 82%, 41%, and 21%, respectively. There were 71 cases in the relief group and 15 cases in the less relief group. Results of the logistic regression analysis showed that the preoperative pain score of SBI (p=0.002; OR: 1.647 (1.199–2.261)) was a relatively independent risk factor for PELD outcomes, and multiplicativity of duration of preoperative symptoms and imaging grade [p=0.004; OR: 1.015 (1.005–1.026)] was a relatively independent risk factor for preoperative presence of numbness and/or weakness. Conclusions. PELD had a good curative effect in the treatment of LDH. Patients of LDH recovered best from pain, followed by numbness and weakness after PELD. Higher level of patients self-reported preoperative pain indicated a better surgical outcome for LDH patients, and preoperative long duration of symptoms together with a severe compression of nerve root significantly increased the risk of presenting numbness and/or weakness.